Controvérsias geográficas: epistemologia e política - José William Vesentini (Confins)
The history of geography is usually thought to be devoid of theoretical controversies. Yet, they existed and they have been important for the building of geographical knowledge. This essay retrieves three meaningful controversies for/of geography. The first one is the misinterpretation between determinism and possibilism. The second one is the famous debate between neopositivists and neokantians about the “excepcionalism” or the specificity of geography as a science. And the third one is the contention between Mackinder and Kropotkin about what is – or should be – geography. These three arguments, as we can see, are not rolling waters, or in other words, problems already solved or overcome. In a certain sense the topics approached by them intersect themselves and are still present. Even more, they are basic subjects and they continue – for several reasons – to share the great epistemological and political questions of geography.